2018
DOI: 10.1186/s12906-017-2072-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual action of highbush blueberry proanthocyanidins on Aggregatibacter actinomycetemcomitans and the host inflammatory response

Abstract: BackgroundThe highbush blueberry (Vaccinium corymbosum) has a beneficial effect on several aspects of human health. The present study investigated the effects of highbush blueberry proanthocyanidins (PACs) on the virulence properties of Aggregatibacter actinomycetemcomitans and macrophage-associated inflammatory responses.MethodsPACs were isolated from frozen highbush blueberries using solid-phase chromatography. A microplate dilution assay was performed to determine the effect of highbush blueberry PACs on A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 95 publications
1
22
0
Order By: Relevance
“…The oral mucosal epithelium plays an important barrier function against microbial infection and invasion. Recently, we reported the ability of tea polyphenols, including epigallocatechin‐3‐gallate and theaflavins, to enhance the integrity of the oral epithelial barrier (Ben Lagha, LeBel, & Grenier, ; Ben Lagha & Grenier, ). In this study, using an oral epithelial cell model, the NDM‐TCP was found to rapidly increase TER values that reflect tight junction integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral mucosal epithelium plays an important barrier function against microbial infection and invasion. Recently, we reported the ability of tea polyphenols, including epigallocatechin‐3‐gallate and theaflavins, to enhance the integrity of the oral epithelial barrier (Ben Lagha, LeBel, & Grenier, ; Ben Lagha & Grenier, ). In this study, using an oral epithelial cell model, the NDM‐TCP was found to rapidly increase TER values that reflect tight junction integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The oral mucosal epithelium plays an important barrier function against microbial infection and invasion. Recently, we reported the ability of tea polyphenols, including epigallocatechin-3-gallate and theaflavins, to enhance the integrity of the oral epithelial barrier (Ben Lagha, LeBel, & Grenier, 2018;Ben Lagha & Grenier, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Wild blueberry consumption has an overall anti-inflammatory effect in the metabolic syndrome [ 76 ]. The antibacterial and anti-inflammatory effects protect the oral keratinocyte barrier as well as neutralize leukotoxin properties of blueberry proanthocyanidins which could be promising candidates as novel therapeutic agents [ 45 ].…”
Section: Preventive Chronic Disease Of Blueberrymentioning
confidence: 99%
“…In the present study, we used the U937-3xκB-LUC human monocytic cell line, which contains a luciferase reporter possessing three NF-κB-binding sites, to evaluate the ability of the designed molecules to inhibit activation of the NF-κB signaling pathway. This model is very convenient to rapidly evaluate the potential of new compounds to block activation of the transcription factor NF-κB, an important regulator of many pro-inflammatory pathways (Cardinal et al, 2017;Lagha & Grenier, 2016;Lagha, LeBel, & Grenier, 2018). First, to exclude the possibility that cell toxicity might have been responsible for any decrease in NF-κB activation, the viability of the U937-3xκB-LUC cells treated with the molecules was evaluated using an MTT test.…”
Section: Biologymentioning
confidence: 99%